2019
DOI: 10.3390/md17050272
|View full text |Cite
|
Sign up to set email alerts
|

Pyrogallol-Phloroglucinol-6,6’-Bieckol from Ecklonia cava Improved Blood Circulation in Diet-Induced Obese and Diet-Induced Hypertension Mouse Models

Abstract: Blood circulation disorders, such as hyperlipidemia and arteriosclerosis, are not easily cured by dietary supplements, but they can be mitigated. Although Ecklonia cava extract (ECE), as dietary supplements, are associated with improving the conditions, there are not many studies verifying the same. In this study, the beneficial effect of ECE and leaf of Ginkgo biloba extract (GBE), which is a well-known dietary supplement, were first confirmed in a diet induced-obese model. Afterwards, 4 phlorotannins were is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 36 publications
0
31
0
Order By: Relevance
“…There have been various animal models developed for investigating these diseases including inbred strains of mice with genetic manipulations that predispose them to disease [120][121][122][123]. Other manipulations and environmental exposures can be used to study the effects of comorbidities such as cigarette smoke-or drug (i.e., bleomycin)-induced pulmonary disease [124,125], paraquat-induced acute renal failure [126], repeated low-dose cisplatin treatment-induced chronic renal failure [127], streptozotocin-developed type I diabetes mellitus [128], and high fat/sucrose dites-induced insulin resistance, which is closely linked with type II diabetes melilitus, obesity, and cardiovascular disease [129,130]. The chemical/diet-induced disease methods can be applied to hACE2 Tg mouse models before infecting the SARS-CoV-2 to elucidate the association between comorbidity and the symptoms or pathogenesis of COVID-19.…”
Section: Validation Of the Risk Factors Associated With The Severe Symentioning
confidence: 99%
“…There have been various animal models developed for investigating these diseases including inbred strains of mice with genetic manipulations that predispose them to disease [120][121][122][123]. Other manipulations and environmental exposures can be used to study the effects of comorbidities such as cigarette smoke-or drug (i.e., bleomycin)-induced pulmonary disease [124,125], paraquat-induced acute renal failure [126], repeated low-dose cisplatin treatment-induced chronic renal failure [127], streptozotocin-developed type I diabetes mellitus [128], and high fat/sucrose dites-induced insulin resistance, which is closely linked with type II diabetes melilitus, obesity, and cardiovascular disease [129,130]. The chemical/diet-induced disease methods can be applied to hACE2 Tg mouse models before infecting the SARS-CoV-2 to elucidate the association between comorbidity and the symptoms or pathogenesis of COVID-19.…”
Section: Validation Of the Risk Factors Associated With The Severe Symentioning
confidence: 99%
“…We added palmitate to hypothalamic neurons and microglia to mimic the environment induced by HFD in the hypothalamus. SFAs directly and quickly trigger inflammation in microglia [24], suggesting that both neurons and microglia are related to the changes in the hypothalamus induced by HFD. First, we evaluated the effect of different concentrations of E. cava extract (ECE) on TLR4 expression in palmitate-treated hypothalamic neurons and microglia.…”
Section: Resultsmentioning
confidence: 99%
“…E. cava extraction and 4 phlorotannins preparation methods were described in Supplementary Materials and Methods and this method followed from previous study [24].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A bioactive fraction of the brown algae Sargassum wightii with optimal antioxidant and ACE inhibition activities (IC 50 56.96 μg/mL) was characterized by Vijayan et al [ 223 ]. An in vivo study evaluated the efficacy of a polyphenol-rich extract from E. cava as well as its major component (pyrogallol-phloroglucinol-6,6-bieckol) for improving blood circulation in diet-induced obese and diet-induced hypertension mouse models [ 224 ]. After four weeks of administering 70 mg and 500 mg of extract/kg bw or 2.5 mg of phenol/kg bw, the study found a reduction in blood pressure and in serum lipoprotein levels in the obese and hypertension mouse models.…”
Section: Bioactive Properties Of Marine Phenolicsmentioning
confidence: 99%